Haematological Studies of the Effects of Nauclea Latifolia Ethanolic Root Extracts in Rats - C, Udeh Sylvester M.; N, Ogugua V.; E, Yakubu O.; J, Parker E.; S, Egba; E, Anaduaka; P, Ugwu O.; M, Ude C.; J, Iornenge T.; J, Danjuma (African Journal of Sciences and Traditional Medicine, 2024)
Nauclea latifolia (Smith) (Family: Rubiaceae) also known as ‘Pin Cushion tree’ or ‘African Peach’ is a struggling shrub, native in tropical Africa and Asia where the use of folk medicine is preval_ent and the search for herbal cure is but common practise. Extraction of the root of Nauclea latifolia with ethanol yielded the ethanol extract. The effects of the ethanolic extract of N. latifolia on haematological parameters showed a significant elevation (p < 0.05) in packed cell volume (PCV), white blood cell count, haemoglobin concentration, red blood cell count and the white blood cell differentials compared to the control group which could be protective mechanisms against infections.